Characterizing Monte Carlo Dropout to Quantify Uncertainty in Trained Neural Networks - Luna, Rafael de S.; Luna, Rodrigo de S.; Figueiredo, Daniel R. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2025: Anais do XXII Encontro Nacional de Inteligência Artificial e ComputacionalDO - 10.5753/eniac.2025.14366, 2025)
Uncertainty quantification is crucial in deep learning applications where reliable decisions depend not only on accuracy but also on predictive confidence. This work investigates Monte Carlo Dropout (MC Dropout), an efficient method to estimate epistemic uncertainty in neural networks. In particular, the influence of its uncertainty parameter is characterized using the California Housing dataset in a regression task. Empirical results reveal that the estimated uncertainty is highly sensitive to this parameter, affecting both the sample average and standard deviation. Interestingly, the error (RMSE) of the model is not monotonic with the uncertainty parameter, indicating an optimal uncertainty value. These findings underscore the need for careful dropout selection during inference and motivate future research on model calibration.